Early and medium‐term outcomes of Alfieri mitral valve repair in the management of systolic anterior motion during septal myectomy. Issue 11 (23rd November 2017) - Collis, Richard; Watkinson, Oliver; Pantazis, Antonis; Tome‐Esteban, Maria; Elliott, Perry M.; McGregor, Christopher G. A.
Abstract: Background: This report studies the early and medium‐term clinical and echocardiographic outcomes of the Alfieri edge‐to‐edge mitral valve repair, as adjunctive therapy, to prevent and treat systolic anterior motion (SAM) at the time of septal myectomy (SM) for left ventricular outflow tract obstruction in hypertrophic cardiomyopathy. Methods: From 2009‐2015, 11 consecutive patients had a trans‐atrial Alfieri repair, to prevent ( n  = 7) or treat ( n  = 4) SAM at the time of SM. Results: No patients were lost to follow‐up. There were no perioperative or late deaths. Pre‐bypass, the mean left ventricular outflow tract gradient, measured directly by simultaneous needle insertion, was 40.7 ± 19.9 mmHg at rest and 115.8 ± 30.4 mmHg on provocation with Isoproterenol, which reduced after SM and Alfieri repair and discontinuation of bypass, to a mean gradient of 8.3 ± 9.8 mmHg at rest and 25.8 ± 9.2 mmHg on provocation. One patient who required mitral valve replacement on day 4, was hospitalized at 2.7 years with heart failure requiring diuresis and remains well at 6 years. One patient developed postoperative atrial fibrillation. There were no other early or late complications. At a median follow‐up of 6.6 years (international quartile range 1.2‐7.4), clinical and echocardiographic data demonstrated maintained improvement in mean New York Heart Association class from 2.6 ± 0.9 preoperatively to 1.7 ± 0.4 and reduction in mean grade of mitral regurgitation from 2.7 ± 0.8 preoperatively to 0.7 ± 0.6. Conclusions: The Alfieri repair, as adjunctive therapy, for the prevention or treatment of SAM at the time of SM demonstrates satisfactory early and medium‐term clinical and echocardiographic outcomes supporting the ongoing utility of this approach.